Chapter 32 The Role of Inclusion, Diversity, Equity, and Access (IDEA) in Agricultural and Biological Engineering - Keshwani, Deepak; Keshwani, Jennifer; Lima, Marybeth (Taylor & Francis, 2025)
Agricultural engineering, developed as an engineering discipline underpinned by physics, applies scientific principles, knowledge, and technological innovations in the agricultural and food industries. During the last century, there was exponential growth in engineering developments, which has improved human wellbeing and radically changed how humans interact with each other and our planet. Among these, “Agricultural Mechanization” is ranked among the top 10 in a list of 20 Top Engineering Achievements of the last century ;that have had the greatest impact on the quality of life. While many success stories abound, the problems of low appeal among students, identity crises, and limited job opportunities in many climes continue to trouble the discipline’s future in many parts of the world. Yet agriculture and agricultural engineering remain fundamental to assuring food and nutrition security for a growing global population. Agricultural, Biosystems, and Biological Engineering Education provides the first comprehensive global review and synthesis of different agricultural, biosystems, and biological engineering education approaches, including a detailed exposition of current practices from different regions. Key Features Describes novel approaches to curriculum design and reform Outlines current and emerging epistemology and pedagogies in ABBE education Provides a framework to grow agricultural engineering in Africa and other developing regions Highlights the role of ABBE education in the context of the SDGs Presented in 3 parts and containing 42 chapters, this book covers the historical evolution of agricultural engineering education and discusses the emergence of biological and biosystems engineering education. It will appeal to engineers and other professionals education planners and administrators, and policy makers in agriculture and other biological industries.